Design of semiconductor/ oxide photoanodes for effective light scattering and charge transfers in dye- sensitized solar cells - Banik, Avishek (My University, 2019)
This Chapter addresses the recent advancements in design and development of photoanodes with various semiconductors/oxides of submicron/micron size of diverse morphology with favorable band alignments, which enhances the light harnessing efficiency of the photoanode by increasing the events of interaction between the sensitizer and the incident light as well as hinders the reverse tunneling of photo-injected electrons. A brief discussion on the evolution of photovoltaic technology, basic architecture and working principle of dye-sensitized solar cells are included. Role of submicron/micron size semiconductors/oxides heterostructures in light harvesting through scattering phenomenon have been discussed.
Qureshi, Mohd.
Keywords: CHEMISTRY